Zgli - Azevedo, Diogo (2023)
Funding Information: The authors acknowledge Fundação para a Ciência e Tecnologia, LASIGE Research Unit, ref. UIDB/00408/2020 and ref. UIDP/00408/2020 and Instituto de Telecomunicações Research Unit, ref. UIDB/50008/2020, and UIDP/50008/2020. The authors also acknowledge the Project PREDICT (PTDC/CCI-CIF/29877/2017), funded by Fundo Europeu de Desenvolvimento Regional (FEDER), through Programa Operacional Regional LISBOA (LISBOA2020), and by national funds, through Fundacção para a Ciência e Tecnologia (FCT), and projects MATISSE (DSAIPA/DS/0026/2019), MONET (PTDC/CCI-BIO/4180/2020) and SmartGlauco (PTDC/CTM-REF/2679/2020). Publisher Copyright: © 2023 by the authors.